2009
DOI: 10.1016/j.bone.2008.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Morpholino-mediated knockdown in primary chondrocytes implicates Hoxc8 in regulation of cell cycle progression

Abstract: Numerous experiments in mutant and transgenic mice have implicated Hox transcription factors in development of the skeletal system, postulating a role for these proteins in cell proliferation of precursor cells and regulation of cell differentiation. Our own data from Hoxc8 and Hoxd4 transgenic mice suggest that Hoxc8 is involved in cell proliferation during cartilage development. In order to directly assess its role in cell proliferation of a specific skeletal cell type, the cartilage-producing chondrocyte, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Of the 55 putative targets, we found that only eight have been empirically validated: miR-378-SUFU, miR-101- MYCN,, and let-7c-TRIM71 (Lewis et al 2003(Lewis et al , 2005Yekta et al 2004;Lee et al 2007;Lin et al 2007;Mitomo et al 2008). Interestingly, many of the 47 remaining putative targets have known CSR functions: proteolysis (miR-101-UBE2A); molecular chaperones (miR-125b-DNAJB2, miR-424-HSPA4L, miR-424-DNAJB4, miR-125b-TTC7A, miR-452-TTC7A, miR-378-TTC7A, miR-378-HSP90AB1, miR-138-CCT5, miR-138-HSPA4L, miR-376a-HSPA6, miR-let-7c-HSPB2, and miR-196a-HSPH1) (Kojima et al 2004;White et al 2005); protein trafficking (miR-125-ZFYVE1); metabolism (miR-382-KYNU, miR-378-KLK4, miR-376a-MAN1C1, miR-let-7c-GALE, and miR-let-7c-RNF20); cell cycle progression (miR-101-MYCN, miR-196a-HOXC8, and miR-196b-HOXC8) (Deraison et al 2007;Kamel et al 2009) (Tables 1 and 2). In addition, several of the annotated TRMs (miR-125b, -138, and -376a) may target AGO2, an integral protein required for miRNA mediated repression (Leung et al 2006) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 55 putative targets, we found that only eight have been empirically validated: miR-378-SUFU, miR-101- MYCN,, and let-7c-TRIM71 (Lewis et al 2003(Lewis et al , 2005Yekta et al 2004;Lee et al 2007;Lin et al 2007;Mitomo et al 2008). Interestingly, many of the 47 remaining putative targets have known CSR functions: proteolysis (miR-101-UBE2A); molecular chaperones (miR-125b-DNAJB2, miR-424-HSPA4L, miR-424-DNAJB4, miR-125b-TTC7A, miR-452-TTC7A, miR-378-TTC7A, miR-378-HSP90AB1, miR-138-CCT5, miR-138-HSPA4L, miR-376a-HSPA6, miR-let-7c-HSPB2, and miR-196a-HSPH1) (Kojima et al 2004;White et al 2005); protein trafficking (miR-125-ZFYVE1); metabolism (miR-382-KYNU, miR-378-KLK4, miR-376a-MAN1C1, miR-let-7c-GALE, and miR-let-7c-RNF20); cell cycle progression (miR-101-MYCN, miR-196a-HOXC8, and miR-196b-HOXC8) (Deraison et al 2007;Kamel et al 2009) (Tables 1 and 2). In addition, several of the annotated TRMs (miR-125b, -138, and -376a) may target AGO2, an integral protein required for miRNA mediated repression (Leung et al 2006) (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Another example is SPP1, which is 87 kb upstream of lncRNA HSP90AA4P (4.155568978 fold downregulation) and a likely candidate as the cis-regulated target of HSP90AA4P. It has been reported that HOXC8 regulated the proliferation of chondrocytes by regulating cell cycles and overexpression of HOXC8 could affect cartilage maturation and endochondral ossification 35,36 . In addition, SPP1, which codes for osteopontin, could enhance the pathological mineralization of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…HOXC8 effects on in vitro surrogate markers of tumorigenesis and progression Overexpression of HOXC genes is associated with prostate cancer (1) and, in the case of HOXC8, increased Gleason grade (22). Recent studies have implicated HOXC8 in the regulation of cell cycle and proliferation (57)(58)(59)(60), apoptosis (58,61), cell differentiation (62-67), cell adhesion (58,61,68), cytoskeleton/motility/migration (61), and tumorigenesis (58,60,61,68,69). On the basis of these reports and the present lack of understanding as to HOXC8 function in prostate carcinogenesis, its effects on in vitro surrogate markers of prostate cell tumorigenicity were examined.…”
Section: Hoxc8 Does Not Directly Interact With Src-3 Ar or Cbpmentioning
confidence: 99%